Canva-based Audio-Visual Media for the Fourth Grade Elementary School Pancasila Formulation Process Material - Septiyani, Vistra; Setiawan, Deni (Universitas Pendidikan Ganesha, 2023)
Students' views on Pancasila Education still need to be more exciting subjects, plus the teacher's method of delivering material is the lecture method. This affects student learning outcomes. This research aims to create Canva-based audio-visual media to improve the learning outcomes of fourth-grade elementary school students. This research is development research using the ADDIE model. The research subjects in this study were 28 elementary school class IVD students, class IVD teachers, and a team of experts (media and materials). Data collection methods use observation, tests, questionnaires, and interviews. Data analysis techniques use quantitative descriptive, qualitative descriptive, and inferential statistics. The research results obtained were 92% material expert testing in the very feasible category, 100% media expert testing in the very feasible category, 92% small group expert testing in the very feasible category, 92.6% large group testing in the very feasible category, and class teacher test 96% with very decent category. The results of the effectiveness test using the paired t-test show that the pre-test and post-test both have an average increase, so it can be concluded that there is a significant difference between the results of the pre-test and post- test for both small and large groups. So, Canva-based audio-visual media on the Pancasila formulation process material is very good, effective, and very suitable for application in learning because it can improve student learning outcomes.